2011
DOI: 10.1186/1471-2164-12-356
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the small RNA component of the transcriptome from grain and sweet sorghum stems

Abstract: BackgroundSorghum belongs to the tribe of the Andropogoneae that includes potential biofuel crops like switchgrass, Miscanthus and successful biofuel crops like corn and sugarcane. However, from a genomics point of view sorghum has compared to these other species a simpler genome because it lacks the additional rounds of whole genome duplication events. Therefore, it has become possible to generate a high-quality genome sequence. Furthermore, cultivars exists that rival sugarcane in levels of stem sugar so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…S1 and S6 A , Supplementary Material online). Despite the lack of Expressed Sequence Tag (EST) evidence for sbi- MIR169 r and sbi- MIR169 s annotation, our previously generated small RNA library from sorghum stem tissue (Calvino et al 2011) supported the transcription from both strands based on small RNA reads mapped to both sbi- MIR169 r and sbi- MIR169 s, respectively (supplementary fig. S6 A , Supplementary Material online).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…S1 and S6 A , Supplementary Material online). Despite the lack of Expressed Sequence Tag (EST) evidence for sbi- MIR169 r and sbi- MIR169 s annotation, our previously generated small RNA library from sorghum stem tissue (Calvino et al 2011) supported the transcription from both strands based on small RNA reads mapped to both sbi- MIR169 r and sbi- MIR169 s, respectively (supplementary fig. S6 A , Supplementary Material online).…”
Section: Resultsmentioning
confidence: 95%
“…To experimentally validate the new MIR169 gene copies found in sorghum through our syntenic analysis among grasses, we mapped previously sequenced small RNAs from sorghum stems (Calvino et al 2011) to the newly predicted MIR169 t/u/v/r/s hairpins. Similarly, to validate the newly described zma- MIR169 s gene copy in maize, we constructed small RNA libraries from endosperm tissue belonging to cultivars B73, Mo17, and their reciprocal crosses (supplementary table S1, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In sugarcane, several protein kinases and transcription factors have been identified that play a role in sucrose accumulation [9]. An involvement of miRNAs (miRNA 169) in regulating stem sugar content in sweet sorghum has also been reported [27].…”
Section: Resultsmentioning
confidence: 99%